Migration of wired network to wireless network technologies / R.Md. Noor and N. Hussin - Noor, R.Md; Hussin, N. (2002)
Wireless technologies allow us to access an Internet, e-mail, printer. etc without to pull a cable through bricks wall or ceiling and across the office or campus to gain the data resources. Today, wireless devices from Palm Pilot to laptop computers to cellular phone with Internet capabilities are exploding in popularity. Wireless LANs use the 802.11 standard to move data through the air at maximum speed of about 11Mbps. Why do we need to migrate from wired network to wireless network? Wireless network offer at least four productivities such as mobility where users can access to real-time information anywhere at anytime in their organization, easy installation and eliminate the need to pull cable, reduced cost of installation which lower investments required for wireless network hardware and long-term cost benefits and wireless LAN able to support variety of network topologies and configurations are easily changed from peer-to-peer network to a small network. Many applications are made possible through the flexibility of wireless network such as universities, retail, health care and manufacturing. This paper will look into possibilities of implementing a wireless LANs network in FSKTM, UM.